The Effect of Green Banking and Green Investment on Firm Value with Eco-Efficiency as Moderation - Murwaningsari, Etty; Rachmawati, Sistya (International Journal of Social and Management Studies, 2023)
The purpose of this research is to analyze the effect of (1) green banking and green investment on firm value. (2) Eco-efficiency moderates green banking and green investment on firm value. This research method was carried out by taking secondary data, namely banks listed on the Indonesian stock exchange (IDX-IC), the number of research samples was 47 banks, according to purposive sampling criteria during the 2016-2021 period (6 years) so the number of samples was 107 observations, using panel data regression. The results of this study (1) Green banking has a positive effect on firm value. (2) Green investment has a positive effect on firm value. (3) Eco-Efficiency can strengthen the effect of green banking on firm value. (4) Eco-Efficiency cannot strengthen the effect of green investment on firm value